2021
DOI: 10.1128/msystems.01125-21
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Selection on Microbiomes To Breed Microbiomes That Confer Salt Tolerance to Plants

Abstract: We developed an experimental protocol that improves earlier methods of artificial selection on microbiomes and then tested the efficacy of our protocol to breed root-associated bacterial microbiomes that confer salt tolerance to a plant. Salt stress limits growth and seed production of crop plants, and artificially selected microbiomes conferring salt tolerance may ultimately help improve agricultural productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Among the dominant classes were Betaproteobacteria followed by Gamma-, Delta- and Alphaproteobacteria ( Jochum et al, 2019 for image). HMME selected microbiome was also found to provide salt tolerance to Brachypodium distachyon ( Mueller et al, 2016 ). Using HMME, specific microbiomes can be engineered to aid wheat and other crop species in mitigating salt, drought, heat, and other types of biotic stresses.…”
Section: Host-mediated Microbiome Engineeringmentioning
confidence: 99%
“…Among the dominant classes were Betaproteobacteria followed by Gamma-, Delta- and Alphaproteobacteria ( Jochum et al, 2019 for image). HMME selected microbiome was also found to provide salt tolerance to Brachypodium distachyon ( Mueller et al, 2016 ). Using HMME, specific microbiomes can be engineered to aid wheat and other crop species in mitigating salt, drought, heat, and other types of biotic stresses.…”
Section: Host-mediated Microbiome Engineeringmentioning
confidence: 99%
“…Bacteria and fungi that are capable of releasing metabolites which trigger plant defence mechanisms against pathogens, insect herbivory, and abiotic stressors are of great interest in crop management. For example, by applying an improved identification and inoculation approach, Mueller et al ( 2021 ) reported a successful selection for rhizosphere microbiomes that confer salt tolerance to the model grass Brachypodium distachyon in greenhouse experiments. Treated plants grown under sodium or aluminum salt stress showed an increase of 55–205% in seed production.…”
Section: Plant Healthmentioning
confidence: 99%
“…The analysis of salt stress tolerance, conferred by the adapted microbial community, was performed by assessing parameters including plant biometrics, stress markers, and bacterial diversity (Anand et al, 2021, Dubey et al, 2022). Similarly, the multi‐passaging approach of rhizospheric engineering was successfully coupled with the ramping‐up of salinity stress, and implemented for nine plant growth cycles, in Brachypodium distachyon , which resulted in salinity stress tolerance in plants after as early as 1–3 passaging cycles (Mueller et al, 2021). The promising results of the above studies emphasize the potential of microbiome‐based approaches to mitigate stress and promote plant growth.…”
Section: Harnessing the Microbiome Of Plantsmentioning
confidence: 99%
“…The 16S rRNA amplicon sequencing of the artificially selected microbiome revealed the abundance of Proteobacteria at the phylum level, specifically β-Proteobacteria (Jochum et al, 2019). Mueller et al (2021) coined the term "differential microbiome-propagation" method for artificial indirect selection of rhizospheric microbiomes and demonstrated improved salt stress tolerance in host plant Brachypodium distachyon using this method. Mitigation of salinity stress in Vigna radiata was witnessed when Anand et al (2021) attempted to adapt the rhizospheric microbiome of the host plant, to salt stress via host-mediated artificial selection by multiple rounds of plant growth under selection pressure (salinity).…”
Section: Synthetic Microbial Communities/consortia (Smc) For Rhizosph...mentioning
confidence: 99%